The Thrreshold of Dedication in Poetry of Saeed kandakji (Journal of Hama University, 2024)
The research presented an applied approach to the threshold of dedication in the poerty of Saeed Kandakji, trying to link it with the containing title(the main title) and the containing titles(the internal titles), adopting the circular mechanism. of the semiotic approach, as it examines the significant patterns formed Following the principles by the threshold sign of dedication as one of the linguistic signs surrounding the text, built to be open in meaning. This threshold served as a link between the containing title and the titles contained in the studied collections, revealing its role in textual cohesion, and highlighting the most important functions assigned to it (aesthetic, eductive, suspenseful, marketing, illustrative), and thereserch also revealed kandakjis creativity during the formation of this threshold, as he piad attention to the color of the font written in it, and was creative with anticipatory drawing, to make it an icon that summarizes the dedication and contains meanings.